Physical Activity and Neurocognitive Health: A Narrative Review - Khatun, Nasima; Paul, Prosanta; Chatterjee, Sridip; Das, Sudip Sundar (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Background: The literature survey shows improvement of cognitive and neurocognitive health through Physical Activity (PA) or exercise. However PA promotes the production of neurotrophins, leads to better brain plasticity. Your brain can decrease in size without use, and can be damaged from stress and depression. Exercise produces neurochemicals which  reverse the damage and increase the size of your brain on the other hand neurons in your brain connect like branches. With exercise, you can increase branch growth and improve brain function so; PA is an essential element for developing cognitive and neurocognitive health.Objective of the study: The specific aim of this review paper is to magnify the effects of physical activity on neurocognitive health.Materials and Method: Numerous related literatures were evaluated for this study from various online database and for screnning of  Prefered reporting items for this narrative study PRISMA 2020 guideline was applied . All appropriate literature that fulfills the primary objective of the study were scientifically presented in this review paper.Results: This review compiles many studies established that regular habit of PA improve neurocognitive health.Conclusion: PA is very much effective for neurocognitive health. Regular involvement in PA improve many neurocognitive domain like: attention span, memory, executive function, social cognition, learning, perception, judgment ability etc.